1993
DOI: 10.1002/neu.480240509
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of vagal sensorimotor circuits during fetal development in rats

Abstract: The differentiation of vagal motor neurons and their emerging central relationship with vagal sensory afferents was examined in fetal rats. To identify peripherally projecting sensory and motor neurons, 1,1'-dioctadecyl-3,3,3'3'-tetramethylindocarbocyanine perchlorate (DiI) was inserted into the proximal gut or cervical vagus nerve in fixed preparations. At embryonic day (E) 12, labeled vagal sensory neurons are present in the nodose ganglia and a few sensory axons project into the dorsolateral medulla. Centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 58 publications
5
56
0
Order By: Relevance
“…With this approach, we observed that nearly all excitatory NTS synapses expressed AMPARs from birth. Glutamatergic synapses formed by primary afferent fibers develop before birth, whereas those made by central projections start to develop few days after birth (Rinaman and Levitt, 1993;Rinaman et al, 2000;Zhang and Ashwell, 2001;Lachamp et al, 2002;Rinaman, 2003). Thus, it is likely that synapses investigated in this study by electrophysiology as well as those analyzed by confocal microscopy belongs to the same population (i.e., primary afferent synapses).…”
Section: Discussionmentioning
confidence: 92%
“…With this approach, we observed that nearly all excitatory NTS synapses expressed AMPARs from birth. Glutamatergic synapses formed by primary afferent fibers develop before birth, whereas those made by central projections start to develop few days after birth (Rinaman and Levitt, 1993;Rinaman et al, 2000;Zhang and Ashwell, 2001;Lachamp et al, 2002;Rinaman, 2003). Thus, it is likely that synapses investigated in this study by electrophysiology as well as those analyzed by confocal microscopy belongs to the same population (i.e., primary afferent synapses).…”
Section: Discussionmentioning
confidence: 92%
“…The ability of exogenous CCK to engage medullary NST neurons and to suppress food intake in 2-day-old rats means that CCK-1 receptor-mediated activation of vagal afferent inputs to the NST and subsequent processes for recruitment of brainstem circuits that underlie CCK-induced hypophagia already are functional. This is not surprising, because anatomical tracing studies revealed a precocious development of vagal viscerosensory inputs to the NST during embryonic development [144]. In newborn rat pups, exogenous CCK causes a significant increase in the excitability of NST neurons that are synaptically activated by electrical stimulation of the subdiaphragmatic vagus nerve, and the increased sensitivity is blocked by a specific CCK-1 receptor antagonist [145].…”
Section: Postnatal Development Of Viscerosensory Inputs To the Endocrmentioning
confidence: 98%
“…Anatomical and functional analyses indicate that the DVC in rats undergoes an early, largely prenatal assembly and maturation of its primary viscerosensory inputs and vagovagal reflex circuitry (Rinaman, Card, Schwaber, & Miselis, 1989;Rinaman & Levitt, 1993;Shapiro & Miselis, 1985){Shapiro, 1985Rinaman, 1989 #138;Rinaman, 1993#505}(Zhang & Ashwell, 2001a. Conversely, hypothalamic and other central neural inputs to the DVC undergo a significant amount of postnatal maturation, together with significant remodeling of local DVC networks (Kawai & Senba, 2000;Lachamp, Tell, & Kessler, 2002;Rao, Jean, & Kessler, 1997;Vincent & Tell, 1999).…”
Section: Postnatal Emergence Of Hypothalamic Inputs To the Dvcmentioning
confidence: 98%